Ответ:
4. x = 1 ; 2 ; 3 ; 4
5. x =
;
; 3 ; 2
Объяснение:
4. (x² - 5x)(x² - 5x + 10) + 24 = 0
Произведем замену: (x² - 5x) = t
Тогда: t(t + 10) + 24 = 0
t² + 10t + 24 = 0
D = 10² - 4·24 = 100 - 96 = 4
; ![t_{2}=\frac{-10-\sqrt{4}}{2} =-6 t_{2}=\frac{-10-\sqrt{4}}{2} =-6](https://tex.z-dn.net/?f=t_%7B2%7D%3D%5Cfrac%7B-10-%5Csqrt%7B4%7D%7D%7B2%7D%20%3D-6)
Произведем обратную размену: t = (x² - 5x)
• (x² - 5x) = -4
x² - 5x + 4 = 0
D = (-5)² - 4·4 = 25 - 16 = 9
; ![x_2 = \frac{5-\sqrt{9}}{2}=1 x_2 = \frac{5-\sqrt{9}}{2}=1](https://tex.z-dn.net/?f=x_2%20%3D%20%5Cfrac%7B5-%5Csqrt%7B9%7D%7D%7B2%7D%3D1)
• (x² - 5x) = -6
x² - 5x + 6 = 0
D = (-5)² - 4·6 = 25 - 24 = 1
; ![x_4 = \frac{5-\sqrt{1}}{2}=2 x_4 = \frac{5-\sqrt{1}}{2}=2](https://tex.z-dn.net/?f=x_4%20%3D%20%5Cfrac%7B5-%5Csqrt%7B1%7D%7D%7B2%7D%3D2)
Ответ: x = 1 ; 2 ; 3 ; 4
5. (x² - 5x + 2)(x² - 5x - 1) = 28
Произведем замену: x² - 5x = t
(t + 2)(t - 1) = 28
t² - t + 2t - 2 = 28
t² + t - 30 = 0
D = 1² - 4·(-30) = 1 + 120 = 121
; ![t_{2}=\frac{-1-\sqrt{121}}{2} =-6 t_{2}=\frac{-1-\sqrt{121}}{2} =-6](https://tex.z-dn.net/?f=t_%7B2%7D%3D%5Cfrac%7B-1-%5Csqrt%7B121%7D%7D%7B2%7D%20%3D-6)
Произведем обратную размену: t = (x² - 5x)
• x² - 5x = 5
x² - 5x - 5 = 0
D = (-5)² - 4·(-5) = 25 + 20 = 45
; ![x_2 = \frac{5-\sqrt{45}}{2} x_2 = \frac{5-\sqrt{45}}{2}](https://tex.z-dn.net/?f=x_2%20%3D%20%5Cfrac%7B5-%5Csqrt%7B45%7D%7D%7B2%7D)
• (x² - 5x) = -6
x² - 5x + 6 = 0
D = (-5)² - 4·6 = 25 - 24 = 1
; ![x_4 = \frac{5-\sqrt{1}}{2}=2 x_4 = \frac{5-\sqrt{1}}{2}=2](https://tex.z-dn.net/?f=x_4%20%3D%20%5Cfrac%7B5-%5Csqrt%7B1%7D%7D%7B2%7D%3D2)
Ответ: x =
;
; 3 ; 2